2007
DOI: 10.1080/00365520601010230
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of colorectal cancer by colonoscopic surveillance in families with hereditary colorectal cancer

Abstract: Objective. In recent years persons at risk for colorectal cancers (CRC) have been subjected to follow-up with colonoscopy in many centres. There is, however, limited knowledge about the effect of such interventions. The objective of this study was to report the results of our observations during the past 15 years. Material and methods. Healthy persons were included in the study according to their family history of CRCs, and prospectively followed with colonoscopies. Results. Altogether, 1133 individuals were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…We have previously reported that regular colonoscopic surveillance may prevent colon cancer (43). Known mutation carriers therefore have a low risk of dying from this disease but are more likely to contract other cancers belonging to the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that regular colonoscopic surveillance may prevent colon cancer (43). Known mutation carriers therefore have a low risk of dying from this disease but are more likely to contract other cancers belonging to the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Here we present the cancer continuum as a circular diagram to reflect that translation is not a linear process and that stages of translation can provide feedback loops to one another. Specific examples of translational research for cancer genetics outlined in table 1[15,16,17,18,19,20,21,22] are based on our portfolio analysis and literature review.…”
Section: Methodsmentioning
confidence: 99%
“…It has become clear that not all families fulfilling the AMSI or AMSII criteria have a detectable MMR mutation [9][10][11], and it has been reported that cancer risk is different in families with an MMR mutation than in families fulfilling the Amsterdam criteria but without indication of an MMR mutation [12,13]. Lindor et al [12] reported lower annual incidence of CRC, later onset of CRC, and a lower incidence of other malignancies in AMSI families in which testing of tumour tissue for microsatellite instability (MSI) showed no abnormalities, compared to AMSI families in which MSI indicated the presence of an MMR mutation.…”
Section: Introductionmentioning
confidence: 99%